Determinants of co-movement and of lead and lag behavior of business cycles in the Eurozone - Duran, H. E.; Ferreira-Lopes, A. (International Review of Applied Economics, 2017)
In this paper we study business cycle correlations in the Eurozone and its determinants. Additionally, we also analyze the determinants of the lead and lag behavior of business cycles in the Eurozone. We explore the relevance, in the Eurozone context, using GDP and employment as the business cycle measures, of the determinants of business cycle synchronization identified in the literature, namely bilateral trade intensity, dissimilarity of labor market rigidity, dissimilarity in industrial structures, financial openness, and foreign direct investment relations. We estimate a simultaneous 4-equations model by Ordinary Least Squares (OLS) and three-stage least square to investigate empirically the above-mentioned determinants of business cycle correlation. Bilateral trade relations present a positive influence on business cycle correlations, while the dissimilarity of labor market rigidity presents a negative influence. The rest of the above-mentioned variables are non-significant. These results are robust to the use of the Hodrick–Prescott-filter and first differences as the de-trending methods, as well as the use of GDP as the business cycle measure, excluding the financial crisis years (2008 and 2009). Results for employment as the business cycle measure are in contrast with the previous ones, and found industrial dissimilarity to be the relevant variable to determine business cycles synchronization. In what concerns the determinants of the lead and lag behavior, results show that the member states of the Eurozone that usually lead the cycle are the ones that are wealthier, with strict employment legislation, more specialized in construction and finance sectors, and more prone to international capital movements. Differences in the determinants between contemporaneous business cycles and lead and lag behavior of business cycles are especially important for policy-makers in the Eurozone to know about, in particular if asymmetric shocks between countries are set in place.